21st Century Prosecutions—Miami-Style Smart Justice. (21st May 2021) - Rundle, Katherine Fernandez; Talpins, Stephen K.
Abstract: Historically, prosecutors and judges relied almost exclusively on punitive measures, most notably jail or prison sentences, to address and deter criminal activity. However, the traditional punitive approach to justice is unduly expensive, does not work as well as it should, and has unnecessary and devastating consequences for lower level offenders and their families. While more and more district attorneys have begun to experiment with what some call "progressive" solutions, strategic remedial measures that reduce crime, improve lives, and save money are a matter of tradition for Miami-Dade County prosecutors. This paper outlines the results of a new strategy in Miami-Dade County, Florida, "Miami-Style Smart Justice" which focuses on a mixture of rehabilitation and incapacitation depending on the circumstances of the offenders as individuals and employs an evidence-based outcome-oriented approach that maximizes public safety, makes judicious use of jail space, minimizes unintended collateral consequences, and reduces costs. Using this approach Miami-Dade County as seen an almost 70% drop in the crime rate since 1993, while dramatically reducing its reliance on incarceration.